Clinical and radiological outcomes of combined modular prothesis and cortical strut for revision proximal femur in giant cell tumor of bone patients. (13th April 2022) - Zhang, Xianghong; Tang, Xianzhe; Li, Zhihong; Zhang, Xiangsheng; Li, Fuming; Tao, Cheng; Liu, Tang
Background: Femoral bone deficiency is a challenging problem in revision proximal femoral replacement. The purpose of this study is to evaluate the clinical and radiological outcomes of revision proximal femoral replacement as a salvage treatment for severe bone loss after oncologic proximal replacement surgery in patient with benign giant cell tumor of bone. Methods: 16 patients (6 men and 10 women) were included in this retrospective study, with a mean age of 46.6 year at the time of revision surgery. All patients underwent revision proximal femoral replacement with the use of modular prosthesis and cortical strut allografts. The modified Harris Hip Score, Short Form 36, and musculoskeletal Tumor Society Score were used for patient evaluation. Regular follow-up was performed to evaluate the recurrence and metastases rate, limb function, and long-term complications of patients. Results: The average follow-up was 46.3 months (range, 26–75 months), during which there was no local recurrence and metastases of patient. At the latest follow-up, the mean modified Harris Hip Score was 70.6 points, which was significantly improved compared with that of preoperative ( p < 0.05). The final follow-up results of Short Form 36, Musculoskeletal Tumor Society Score, and limb-length discrepancy were also significantly improved compared to that of preoperative ( p < 0.05). At the latest follow-up, the implanted femoral stems were all stable and all cortical strut allografts were also incorporated to their own bone. Conclusion: Using modular prosthesis and cortical strut allografts in revision, proximal femur replacement is an acceptable procedure for relatively young patient with severe proximal femoral bone loss after oncologic surgery with benign giant cell tumor of bone. More attentions should be paid to reduce the risk of complications in these complex reconstructions.